Hospital-based violence intervention programs targeting adult populations: an Eastern Association for the Surgery of Trauma evidence-based review. Issue 1 (28th September 2016) - Affinati, Steven; Patton, Desmond; Hansen, Luke; Ranney, Megan; Christmas, A Britton; Violano, Pina; Sodhi, Aparna; Robinson, Bryce; Crandall, Marie; ,
Abstract : Background: Violent injury and reinjury take a devastating toll on distressed communities. Many trauma centers have created hospital-based violent injury prevention programs (HVIP) to address psychosocial, educational, and mental health needs of injured patients that may contribute to reinjury. Objectives: To evaluate the overall effectiveness of HVIPs for violent injury prevention. We performed an evidence-based review to answer the following population, intervention, comparator, outcomes (PICO) question: Are HVIPs attending to adult patients (age 18+) treated for intentional injury more effective than the usual care at preventing: intentional violent reinjury and/or death; arrest and/or incarceration; substance abuse and/or mental issues; job and/or school attainment? Data sources: PubMed, Web of Science, Google Scholar, and the Cochrane Library were queried for salient articles by a professional librarian on two separate occasions, and related articles were identified from references. Study eligibility criteria, participants, interventions: Eligible studies examined adult patients treated for intentional injury in a hospital-based violence prevention program compared to a control group. Study appraisal and synthesis methods: We used the Grading of Recommendations Assessment, Development, and Evaluation methodology to assess the breadth and quality of the evidence. Results: 71 articles were identified. After discarding duplicates, reviews, and those articles that did not address our PICO questions, we ultimately reviewed 10 articles. We found insufficient evidence to recommend adult-focused HVIP interventions. Limitations: There was a relative paucity of data, and available studies were limited by self-selection bias and small sample sizes. Conclusions: We make no recommendation with respect to adult-focused HVIP interventions.